Tuku Umur (AnalisisFaktorPerkawinan Anak di Panuggalan, Grobogan) - Kushidayati, Lina; l Hadi, Abdul; Baroroh, Umul (PALASTREN: Jurnal Studi Gender, 2021)
This article discusses about the practice of child marriage in Grobogan and its factors. he factors supporting child marriage in Grobogan include; economic, education, socio-culture and the understanding of religious manuscripts. Meanwhile, from the analyzed copy of the judge's decision on the application for marriage dispensation, the reason often put forward by the applicant is that marrying is to prevent committing adultery. From the socio-cultural perspective, the condition of the people of Panunggalan village plays an important role in the occurrence of child marriage. Owing to the condition of an agrarian society that relies on rainwater for agriculture and low levels education and income, child marriage is considered as a way out of poverty and life's difficulties. In the theory of patriarchal connectivity, family members have a very close relationship so they always try to help each other and together maintain family values. In such conditions, children do not feel oppressed when they are married at a child's age because it is a form of maintaining family collectivity. Keywords: child marriage, factors, women